Application an internet facilitation in a community-based cervical cancer screening project - Hui Du; Xinfeng Qu; Guixiang Wang; Chunlei Guo; Zhaohui Wang; Juan Min; Zhihong Liu; Qicai Hu; Hongxue Luo; Chun Wang; Xia Huang; Yun Chen; et al. (BMC, 2023)
Abstract Objective To evaluate the feasibility of an internet-facilitated community model for cervical cancer screening using self-collected HPV testing as primary screening. Method A population-based cervical cancer screening program was conducted in the suburb of Shenzhen, China, from September 2014 to July 2017. Women with 25-60 years of age and no pregnancy were eligible for participation. Participants could register for screening by logging in a website by themselves or with the aids of local community workers. A unique barcode was issued to each applicant upon successful registration. After registration, women could get sampling kits from community screening site/study clinic, collect vaginal samples privately or in group, and provide their sample for Hr-HPV tests on Cobas4800 and SeqHPV assays. Testing reports were checkable through personal account for all participant and phone calls were given to all women positive of Hr-HPV. Participants positive of both or either the 2 assays were identified as the positives. The positives could return the study clinic for triage or search medical care in other clinics. Colposcopy directed or ramdom biopsies were performed on all positives who returned to the study clinics. Results A total of 10,792 community women registered for screening, among whom, 10,010 provided their vaginal samples for tests. 99.5% of the participants were confirmed to have correct personal identifiable information and samples, and 98.9% of them got HPV testing results from both or either assays. No adverse event was reported. Conclusion When self-collected HPV testing is used as the primary testing, the internet-based data platform facilitates the screening in registration, data collection, and data tracking, and increases the screening coverage. Internet-facilitated community model is promising to cervical cancer control and applicable in regions with variety of resources.